2020
DOI: 10.1186/s13227-020-00158-7
|View full text |Cite
|
Sign up to set email alerts
|

Volvox and volvocine green algae

Abstract: The transition of life from single cells to more complex multicellular forms has occurred at least two dozen times among eukaryotes and is one of the major evolutionary transitions, but the early steps that enabled multicellular life to evolve and thrive remain poorly understood. Volvocine green algae are a taxonomic group that is uniquely suited to investigating the step-wise acquisition of multicellular organization. The multicellular volvocine species Volvox carteri exhibits many hallmarks of complex multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 78 publications
0
44
0
Order By: Relevance
“…popular model organism of developmental biology-a number of review articles in recent years are devoted to the above-mentioned aspects of ontogeny of this alga (Herron, 2016;Matt and Umen, 2016;Desnitskiy, 2018Desnitskiy, , 2019Desnitskiy et al, 2018;Umen, 2020;etc. ).…”
Section: Methods and Models Of Developmental Biologymentioning
confidence: 99%
“…popular model organism of developmental biology-a number of review articles in recent years are devoted to the above-mentioned aspects of ontogeny of this alga (Herron, 2016;Matt and Umen, 2016;Desnitskiy, 2018Desnitskiy, , 2019Desnitskiy et al, 2018;Umen, 2020;etc. ).…”
Section: Methods and Models Of Developmental Biologymentioning
confidence: 99%
“…Unfortunately, we were unable to synchronize B. braunii cells of either race. Although cells in other colonial algae like Volvox or Haematococcus pluvialis are able to be synchronized [84,85], there are no other reports of synchronization for B. braunii. A difference between our study and that of Hirose et al [25] is the strain of the A race used; they used a race A strain from the Culture Collection of Algae at the University of Texas (UTEX 2441), while we used the A race Yamanaka strain [5].…”
Section: Synchronization Of B Braunii Culturesmentioning
confidence: 98%
“…The volvocines have unicellular members, such as the well-studied model alga Chlamydomonas reinhardtii, and dozens of larger multicellular or colonial forms that are organized into genera based on cell number, morphology and organismal size. The most complex volvocine species are in the genus Volvox where individuals can have thousands of cells and exhibit full or partial germ-soma differentiation (Umen 2020). Molecular phylogenetic analyses have revealed that several volvocine genera, including Volvox, are polyphyletic (Herron and Michod 2008).…”
Section: Volvocine Algaementioning
confidence: 99%